2‐Trifluoromethyl‐2‐Hydroxypropionamide Derivatives as Novel Reversal Agents of ABCG2 (BCRP)‐Mediated Multidrug Resistance: Synthesis and Biological Evaluations. Issue 8 (25th April 2017) - Kathawala, Rishil J.; Li, Tianwen; Yang, Danwen; Guo, Hui‐Qin; Yang, Dong‐Hua; Chen, Xiang; Cheng, Changmei; Chen, Zhe‐Sheng
ABSTRACT: It has been postulated that one of the biggest impediments to a successful chemotherapy is the phenomena of multidrug resistance (MDR) in cancer cells. One of the main mechanisms of MDR is overexpression of the ATP‐binding cassette (ABC) transporters in cancer cells which alters absorption, distribution, metabolism, and excretion of various chemotherapeutic drugs. Efforts have been made to find effective inhibitors of ABC transporters. However, none has been approved clinically. This study shows that a novel compound 3‐chloro‐N‐(2‐hydroxyphenyl)‐4‐(3, 3, 3‐trifluoro‐2‐hydroxy‐2‐methylpropanamido) benzamide (compound 7d), one of the 2‐trifluoromethyl‐2‐hydroxypropionamide derivatives could reverse ABCG2 (BCRP)‐mediated MDR. Cytotoxicity studies show that compound 7d sensitizes the ABCG2‐overexpressing cells to chemotherapeutic drugs mitoxantrone and SN‐38, which are well‐established substrates of the ABCG2 transporter. Western blotting results indicate that compound 7d does not significantly alter the protein level of the ABCG2 transporter. Accumulation and efflux studies demonstrate that compound 7d increases intracellular accumulation of mitoxantrone by inhibiting the function of ABCG2. Overall, these findings indicate a potential use for compound 7d as an adjuvant agent for chemotherapy to inhibit the function of the clinically relevant ABC transporter and sensitize tumor cells to chemotherapeutic drugs. J. Cell. Biochem. 118: 2420–2429, 2017. © 2017 Wiley Periodicals, Inc. Abstract : We demonstrated that novel 2‐triﬂuoromethyl‐2‐hydroxypropionamide derivatives could significantly reverse ABCG2‐mediated multidrug resistance in both drug selective human non‐small cell lung cancer cells and stably transfected ABCG2‐overexpressing cell models. 2‐triﬂuoromethyl‐2‐hydroxypropionamide derivatives do not change the expression levels of ABCG2 protein but act by inhibiting the function of the transporter.